Minat Penggunaan Peer To Peer Lending : Bukti Empiris Berbasis Kesadaran Konsumsi Islami & Literasi Keuangan Digital - Fatmawati; Munawarah; Muh Hasbi Ash Shiddiq (Institut Agama Islam Negeri Bone, 2026)
The digital transformation of the financial industry through peer-to-peer (P2P) lending has triggered a shift toward consumptive funding behavior, creating a gap between financial technology adoption and financial behavior control in Bone Regency. The practicality of online loans often obscures financial rationality and ethical transaction values of the community. This study aims to analyze and explain the influence of Islamic consumption awareness and digital financial literacy on the interest of the Bone Regency community in using P2P lending services. The research method applied is causal associative quantitative. Sampling was conducted using a purposive sampling technique, resulting in 84 productive-age respondents. Data processing was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method, assisted by SmartPLS 4 software. The results show that Islamic consumption awareness has a negative and insignificant effect on the interest in using P2P lending (β = -0.131; t = 0.954; p = 0.340). Conversely, digital financial literacy is proven to have a positive and highly significant effect on the interest in using P2P lending (β = 0.632; t = 4.887; p = 0.000). Simultaneously, both exogenous variables contribute 28.1% to the variance of interest in using the service. These findings reflect a dualism of orientation in the local community, where the appeal of digital feature practicality (cognitive push) is currently proven to be more dominant in influencing adoption interest compared to spiritual normative constraints (spiritual pull).